Attitudes of Farmers Towards Improvement Methods of Field Irrigation Systems at Some Villages in Al-Bustan Region, El-Beheira Governorate in Arabian Republic of Egypt - Ghozlan, Ahmed Mohamed Ali (Journal of agricultural, environmental and veterinary sciences, 2023)
This research aimed to determine the attitude of respondents’ farmers towards improvement methods of field irrigation systems, to study the correlation between the degree of their attitudes towards those methods and the independent variables studies, and finally to identify the most important problems facing the respondents’ farmers when applying improvement methods of field irrigation systems from their view point. This research was conducted in Al-Bustan Area, as it is representative of the new reclaimed lands, it includes Al-Bustan and Al-Entlaq Surveillance, two villages were selected from each surveillance. The selected villages were Tawfik al-Hakim and Abbas al-aqqad in The Al-Bustan surveillance and al-safa, al-Marwa, and Abd al-Azeim Zaher in the Al-Entlaq surveillance. A random sample of 203 respondents was selected, they represent 10% according to the Herbert Arken equation of the total number of farmers in each of the four selected villages. The frequencies, percentages, and average arithmetic, standard deviation, weighted, average score, and person correlation coefficient were used in data analysis and presentation of the results. The results of the research could be summarized as follows: 1. 36.5% of the respondents’ farmers had a positive attitude. 44.8% of them had a neutral attitude, and 18.7% of them showed negative attitude towards improvement methods of field irrigation systems. 2. Combined four independent variables morally related with the degree of the researches’ attitudes towards improvement methods of field irrigation systems, which are the respondent’s education, the degree of prepare for change, the degree of knowledge of improvement methods of field irrigation systems, and the degree of indecision on agricultural services centers. 3. The most important problems are facing the respondents’ farmers when applying improvement methods of field irrigation systems for high financial funding, it is difficulty to provide by small-scale farmers, the high costs of lining irrigation ditches, and the need for mobile sprinkler irrigation system to big regular maintenance to ruin it quickly.